Crusted Scabies in Post-Disaster - Salsabila, Wizar Putri Mellaratna (Integrative Perspectives of Social and Science Journal, 2026)
Crusted scabies is a severe and highly contagious variant of scabies caused by Sarcoptes scabiei var. hominis, characterized by massive mite proliferation, hyperkeratosis, and widespread crusted skin lesions. This condition poses a major public health threat, particularly in post-disaster settings where overcrowding, poor sanitation, limited access to clean water, and disrupted healthcare systems facilitate rapid transmission. This study aims to review the characteristics, risk factors, clinical manifestations, diagnosis, and management of crusted scabies in post-disaster environments based on current dermatological literature. In such settings, additional factors including malnutrition, immunosuppression, chronic illness, and psychological stress increase susceptibility and may accelerate progression from classic to crusted scabies. Clinically, crusted scabies differs from the classic form by minimal or absent pruritus, extensive hyperkeratotic plaques, and frequent nail involvement, often leading to delayed diagnosis. Confirmation is primarily achieved through skin scraping, which typically reveals abundant mites and eggs. Management requires an aggressive and comprehensive approach, combining systemic therapy (oral ivermectin), topical scabicides (e.g., permethrin), and keratolytic agents, alongside treatment of close contacts and strict environmental decontamination. In disaster settings, coordinated public health strategies—including surveillance, mass treatment, and health education—are essential to control outbreaks. In conclusion, crusted scabies in post-disaster conditions represents a preventable yet potentially severe disease. Early recognition, appropriate treatment, and integrated public health interventions are critical to reducing morbidity and preventing widespread transmission in vulnerable populations.